Compulsory Conciliation in Canada: Do We Need It? - Misick, John (Relations industrielles / Industrial Relations, 1978)
This paper tries to find support for the proposition that a free system of conciliation would be (a) more effective and (b) les s costly in the long run than a compulsory one.